Correction: Mitochondrial phosphate transporter and methyltransferase genes contribute to Fusarium head blight Type II disease resistance and grain development in wheat. - Keshav B Malla; Ganesh Thapa; Fiona M Doohan (PLoS ONE, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0258726.].